Targeting Adiposity and Inflammation With Movement to Improve Prognosis in Breast Cancer Survivors (The AIM Trial): Rationale, Design, and Methods - Kang, Dong-Woo; Wilson, Rebekah L.; Gonzalo-Encabo, Paola; Norris, Mary K.; Hans, Marybeth; Tahbaz, Meghan; Dawson, Jackie; Nguyen, Danny; Normann, Amber J.; Yunker, Alexandra G.; Sami, Nathalie; Uno, Hajime; et al. (Frontiers in Oncology, 2022)
Background: Obesity is a significant contributor to breast cancer recurrence and mortality. A central mechanism by which obesity stimulates cancer progression is through chronic, low-grade inflammation in adipose tissue. Exercise interventions to target chronic inflammation has a potential to improve obesity- and breast cancer-related outcomes; however, no studies have investigated the roles of exercise in modulating adipose tissue inflammation in breast cancer survivors. Also, it is unclear which exercise prescription would be optimal to maximize the outcomes. Therefore, we designed a randomized controlled trial (Taking AIM at Breast Cancer: Targeting Adiposity and Inflammation with Movement to Improve Prognosis in Breast Cancer Survivors [AIM] Trial) to examine the mechanisms by which different modalities of exercise impact chronic inflammation as a biomarker of breast cancer prognosis. Methods: The AIM trial is a prospective, three-armed, phase II randomized controlled trial investigating the effects of a 16-week supervised circuit aerobic and resistance exercise (CARE) program versus a traditional aerobic and resistance exercise (TARE) program and attention control (AC) on adipose tissue inflammation in breast cancer survivors. 276 patients who are diagnosed with stage 0-III breast cancer, post-treatment, sedentary, and centrally obese are randomized to one of the three groups. The CARE and TARE groups participate in thrice-weekly supervised exercise sessions for 16 weeks. The AC group are offered the CARE program after the intervention period. The primary endpoint is adipose tissue inflammation assessed by core biopsy and blood draw. The secondary and tertiary endpoints are sarcopenic obesity, physical fitness and function, and patient reported outcomes. The exploratory outcomes are long-term breast cancer outcomes. Discussion: This is the first randomized controlled trial examining the effects of exercise on adipose tissue inflammation in obese, breast cancer survivors. Our findings are anticipated to contribute to a better understanding of exercise modalities and mechanisms on adipose tissue inflammation that can potentially improve breast cancer prognosis.